Pengembangan Media Pembelajaran Patarmin dalam Meningkatkan Kemampuan Penalaran Matematika - Safari, Safari (SCAD Independent, 2024)
This study aims to describe: (1) mathematical reasoning ability before learning with PATARMIN media; (2) the learning process using PATARMIN media; (3) students' responses to learning; and (4) mathematical reasoning ability after learning using PATARMIN learning media. This type of research is development research with the ADDIE model. Data were collected through tests, interviews, questionnaires and documentation. Data were analyzed descriptively quantitatively and qualitatively. The results of the study show: 1) Students' mathematical reasoning ability before learning with PATARMIN media is classified as low; 2) Things that teachers do are: grouping students, distributing media and student worksheets, orientation of media use, guiding students to conduct experiments, expanding the concepts obtained, drawing conclusions, and evaluation; 3) With PATARMIN media, students are motivated to learn, understand the subject matter, can practice building knowledge themselves, and can solve problems well; 4) Mathematical reasoning ability after being taught with PATARMIN media is classified as good. Aspects that are classified as high are the indicators of the ability to provide explanations through pictures and estimate answers, while those that are classified as low are checking the validity of arguments and drawing conclusions.